Umiejętność czytania ze zrozumieniem w świetle wyników badań – implikacje dla strategii edukacyjnych - Czapla, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2025)
The article presents the latest research findings on the interrelationship between the type of text medium and the ability to read with understanding acquired through education. A large-scale study by researchers has shown that the kind of medium impacts reading comprehension. Researchers have proven that reading from digital media negatively affects reading comprehension in the early stages of education. Naomi S. Baron attempted to explain this phenomenon. She pointed to two different reading techniques. The study concludes that education, especially early childhood education, should provide reading instruction from printed texts, which determines the fate of textbooks, and should not be abandoned. The study of academic reading was also analysed. The study revealed a high level of affirmation of the advantages of reading in print. Nearly 92% of respondents said they concentrate best when reading in print. The results of our survey of high school graduates studying medicine, computer science, pedagogy, and physical culture sciences confirmed the need to use textbooks in the educational process. The printed text was and still is the primary didactic medium.